Studies on the inheritance pattern of bacterial spot (Xanthomonas vesicatoria) in tomato - Sharma, Deepa; Gupta, S.K.; Jarial, Kumud (Indian Phytopathology, 2011)
Bacterial spot caused by Xanthomonas vesicatoria is an important bacterial disease of tomato causing fruit losses as high as upto 52 per cent. The development of resistant strains against chemicals has emphasized the need for breeding resistant varieties. Four tomato lines viz. Hawaii-7998, CRA-66, FT-5 and Solan Vajr were screened for bacterial spot resistance under artificial inoculation conditions. The experiment on the genetics of resistance to bacterial spot on lines Hawaii-7998 (resistant) and CRA-66 (moderately resistant), susceptible lines, FT-5 and Solan Vajr and their F1s’, BC1, BC2 and F2s were carried out under field conditions. Results revealed that resistance to bacterial spot in both the lines was governed by polygenes. The additive and dominance effect of genes played an important role in the inheritance of this disease.